0

# How do I do this problem using the substitution method. x - 9y = -66, -x - 5y = -46

How do I do this problem using the substitution method. x - 9y = -66, -x - 5y = -46

### 2 Answers by Expert Tutors

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...
4.8 4.8 (4 lesson ratings) (4)
0
X -9Y = -66
-X -5Y = -46                   Solve one the the variables in terms of other, and substitute in the other equation.
and becomes equation with one variable/

X = 46 - 5Y   from 2nd equation.

46 - 5 Y - 9Y = -66

66 + 46  = 14 Y

112 = 14 Y

Y = 112/ 14 = 8

Substitute back into 1st equation:

X = 46 - 5(8) = 8

X =  6
Vivian L. | Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACHMicrosoft Word/Excel/Outlook, essay comp...
3.0 3.0 (1 lesson ratings) (1)
0
Hi Quanda;

Let's take the first equation...
x - 9y = -66
Let's isolate x by adding 9y to both sides...
9y+x-9y=-66+9y
x=-66+9y

Let's substitute this into the other equation...
-x - 5y = -46
-(-66+9y)-5y=-46
A negative of a negative number results in positive, -(-66)=66 and
a negative of a positive number results in negative, -(9y)=-9y.
66-9y-5y=-46
66-14y=-46
Let's subtract 66 from both sides...
-66+66-14y=-46-66
-14y=-112
Let's divide both sides by -14...
(-14y)/-14=-112/-14
A negative number divided by a negative number results in a positive number.
y=8

x - 9y = -66, -x - 5y = -46
x-9y=-66
Let's plug-in y=8...
x-[9(8)]=-66
x-72=-66
Let's add 72 to both sides...
72+x-72=-66+72
x=6

The second equation...
-x-5y=-46
Let's plug-in y=8 and x=6 to verify...
-6-[5(8)]=-46
-6-40=-46
-46=-46